The complete mitochondrial genome of Dudusa sphingiformis (Lepidoptera: Notodontidae) and phylogenetic analysis - Feng Zhou; Liyuan Yao; Zhibo Hou; Peng Yu; Lingyun Chen; Junyu Liang (Mitochondrial DNA. Part B. Resources, 2021)
Dudusa sphingiformis is an important lepidopteran pest widely distributed in tropical and subtropical zones of Asia. In this paper, the complete mitochondrial genome (mitogenome) of D. sphingiformis was determined by next-generation sequencing. The mitogenome was 15,806 bp in length, comprising 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and an AT-rich control region (D-loop). The gene arrangement of this mitogenome was identical to that of the previous studies of Notodontidae moths. Almost all the PCGs initiated with typical ATN codons, except for cox1 with CGA. Among them, nine PCGs terminated with TAA or TAG, while other four PCGs (cox1, cox2, nad5, and nad4) with incomplete stop codon T. All the 22 tRNAs had the typical cloverleaf structure, except for trnS1, whose dihydrouridine (DHU) arm forms a simple loop. Phylogenetic analysis based on the concatenated nucleotide sequences of 13 PCGs indicated that D. sphingiformis was more closely related to other species of family Notodontidae, forming a monophyletic group, with well-resolved relationships among five family of Noctuoidea.